International comparative advantage in manufacturing : changing profiles of resources and trade (Vienna : United Nations Industrial Development Organization, 1986)
The book aims to provide the formulators of industrial and economic policies with empirical findings concerning international comparative advantage in manufacturing.
rpm 23/01/2019
Loans
Keywords: Manufacturing